2(x+3)=5(x-1)-7(x-3)+2
axllxa:
Ya esta ahi te va la solucion...
Respuestas
Respuesta dada por:
14
2(x+3)=5(x-1)-7(x-3)+2
2x+6=5x-5-7x+21+2
2x+6=5x-7x+21+2-5
2x+6= -2x+23-5
2x+6= -2x+18
2x+2x=18-6
4x=12
x=12/4
x=3
2x+6=5x-5-7x+21+2
2x+6=5x-7x+21+2-5
2x+6= -2x+23-5
2x+6= -2x+18
2x+2x=18-6
4x=12
x=12/4
x=3
Respuesta dada por:
11
Hi te vala solucion...cualquier duda me avisas
Adjuntos:
![](https://es-static.z-dn.net/files/db8/d49bde44855e98830d40fc71c1d88df8.jpg)
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años